ANALISIS PERKEMBANGAN PENDAPATAN ASLI DAERAH KABUPATEN BATANGHARI - Elsa Febri Yenti; Rahma Nurjanah; Jaya Kusuma Edy (STKIP Subang, 2026)
This study aims to analyze the development of Locally Generated Revenue (PAD), the structure of its components, and its contribution to the Regional Budget (APBD) of Batanghari Regency during the 2015–2024 period. This study uses a qualitative descriptive analysis method utilizing secondary data in the form of time series data obtained from the Batanghari Regency Central Statistics Agency (BPS), the Regional Finance Agency's APBD realization report, and various other supporting documents. The analysis was conducted on PAD targets and realizations, which consist of regional taxes, regional levies, proceeds from the management of separated regional assets, and other legitimate PAD. The results show that the development of Batanghari Regency's PAD fluctuates and is unstable. The average PAD realization only reached 67.06% of the budget target. The PAD contribution to the APBD is also relatively low, averaging 8.32%, indicating that the region's level of fiscal independence is still low and it remains dependent on central government transfer funds. The components of Regional Original Revenue (PAD), consisting of regional taxes, regional levies, proceeds from the management of separated regional assets, and other legitimate PAD, also show fluctuating developments. Based on the research findings, local governments need to optimize PAD management by increasing the effectiveness of tax and levy collection, strengthening oversight, digitizing the regional revenue system, and setting more realistic budget targets to increase PAD's contribution to the Regional Budget (APBD). Keywords: Regional Original Revenue (PAD), APBD, PAD contribution, Batanghari Regency